System Support in Counselling among Muslim Convert Clients in Malaysia - Samsiah, Jayos; Faizah, Abd Ghani; Lokman, Mohd Tahir; Kamarul Azmi, Jasmi; Nur Fatihah, Abdullah Bandar (Faculty of Cognitive Sciences and Human Development, Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to identify the use of external support systems by counsellors located at the Council within the Islamic Religious Department in Malaysia. Data for this research was collected using a case study. The case study included an interview of five (5) registered counsellors in Islamic Organization in Malaysia. This study was based on a qualitative approach and data were analyzed using N’Vivo 7.0. The data were developed into appropriate themes and sub-themes. The study revealed that the external support system (community support, peer counsellor, Islamic law and Islamic organization) should be applied to Muslim counsellors and Muslim converts. This research could be used as a guide for a counsellor to be more robust in providing guidance and counselling services to specific clients, such as, new Muslim converts.